Laboratory manual of organic chemistry - Čižmáriková, Ružena, 1947- (Comenius University in Bratislava, 2012)
This manual includes general instruction for work in the chemical laboratory. For example: purification techniques, identification and characterization of organic compounds, molecular modeling, synthesis of organic compounds, equipment of laboratory desk, chemicals for practical exercises.